BANTUAN ALAT TANGKAP DAN SOSIALISASI PERATURAN PERUNDANG-UNDANGAN BIDANG KELAUTAN DAN PERIKANAN TENTANG ALAT TANGKAP RAMAH LINGKUNGAN BAGI NELAYAN KECAMATAN UJUNGPANGKAH, GRESIK - Muh. Sulaiman Dadiono; Suhaili, Suhaili; Andi Rahmad Rahim; Aminin, Aminin (Abdi Jaya : Jurnal Pengabdian Indonesia, 2026)
Ujungpangkah District, Gresik Regency, is one of the strategic coastal areas in East Java with significant potential for capture fisheries. However, fishermen's productivity still faces various obstacles, including limited fishing gear that complies with the principles of sustainability and fishermen's low understanding of maritime and fisheries laws and regulations. This community service program was implemented on March 1, 2018, through a collaboration between the Ministry of Maritime Affairs and Fisheries (KKP), Commission VI of the Indonesian House of Representatives (DPR RI) for the 2014–2019 period, and the Gresik Regency Fisheries Office, targeting 150 fishermen in Ujungpangkah District. The activity aims to increase catch productivity by providing assistance with environmentally friendly fishing gear while strengthening fishermen's legal knowledge regarding the use of fishing gear that does not damage the marine ecosystem. Implementation methods include socialization, lectures, interactive discussions, distribution of fishing gear, and participatory evaluation. The results of the activity show an increase in fishermen's understanding of the importance of environmentally friendly fishing gear, increased access to legal and productive fishing equipment, and the emergence of hopes for increasing catches without damaging fishery resources. The main obstacles were the absence of several fishing groups and protests from fishermen who had not yet received assistance. Overall, the program had a positive impact on strengthening the fishing economy and conserving the coastal environment.